2020
DOI: 10.3389/fgene.2020.00849
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Long Non-coding RNAs in Autism Spectrum Disorders

Abstract: Genetic and environmental factors, alone or in combination, contribute to the pathogenesis of autism spectrum disorder (ASD). Although many protein-coding genes have now been identified as disease risk genes for ASD, a detailed illustration of long non-coding RNAs (lncRNAs) associated with ASD remains elusive. In this study, we first identified ASD-related lncRNAs based on genomic variant data of individuals with ASD from a twin study. In total, 532 ASD-related lncRNAs were identified, and 86.7% of these ASD-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Considering the importance of lncRNAs in neuronal physiology it is not surprising that dysregulation of lncRNAs in the brain might be linked to neurodevelopmental disorders [ 160 , 161 ], autism spectrum disorders [ 162 , 163 , 164 ], substance use [ 165 ], intellectual disability [ 166 ], neurodegenerative diseases and neurological disorders [ 167 , 168 ]. A growing number of studies report that lncRNAs are associated with the pathology and development of neurodegenerative diseases [ 80 , 114 , 169 , 170 ].…”
Section: Lncrnas In Brain Disease and Neurodegeneration: Biomarkers Or Active Players?mentioning
confidence: 99%
“…Considering the importance of lncRNAs in neuronal physiology it is not surprising that dysregulation of lncRNAs in the brain might be linked to neurodevelopmental disorders [ 160 , 161 ], autism spectrum disorders [ 162 , 163 , 164 ], substance use [ 165 ], intellectual disability [ 166 ], neurodegenerative diseases and neurological disorders [ 167 , 168 ]. A growing number of studies report that lncRNAs are associated with the pathology and development of neurodegenerative diseases [ 80 , 114 , 169 , 170 ].…”
Section: Lncrnas In Brain Disease and Neurodegeneration: Biomarkers Or Active Players?mentioning
confidence: 99%
“…It is reported that the annual incidence of ASD is between 1 and 3% ( 3 ). The prevalence of ASD is sex imbalance with a distribution of three males to one female ( 4 , 5 ). ASD often impairs social skills and autonomy, causing ASD children with difficulty in social, speech, and behavioral skill development.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of ASD patients are reported to have an identifiable genetic cause ( 8 ). The characteristics of highly genetic heterogeneity made the pathophysiology of ASD really elusive ( 4 ). MicroRNAs (miRNAs) are short noncoding RNAs with 18–25 nucleotides, playing an important role in regulating gene expression of ASD patients ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the worldwide prevalence of ASD is between 1% and 3% of the general population [3] . The prevalence of ASD is sex imbalance, with a distribution of three males to one female [4] . In most cases, ASD symptoms are rst recognized in early childhood, with an average diagnosis age of 4 years [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of ASD patients were reported to have an identi able genetic cause [8] , with estimated genetic contributions accounting for > 50-60% of ASD risk [5] . The characteristics of highly genetic and phenotypic heterogeneity made the pathophysiology of ASD really elusive [9] . Noncoding RNA is a crucial player involved in regulating chromatin structure and gene expression of ASD patients [10] .…”
Section: Introductionmentioning
confidence: 99%